Development of E-Learning Based on Flipped Classroom Assisted with Blog on Momentum and Impuls Materials Physics in Class X High Schools - Yellyn Septiani; Misdalina Misdalina; Linda Lia (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2021)
This research aims to produce e-learning based on flipped classrooms using blogs and potentially impact high school students on momentum and impulse material. This study uses the ADDIE model which consists of several stages, namely analysis, design, development, implementation, and evaluation. The evaluation stage is carried out in the form of a formative evaluation which consists of several stages, namely self-evaluation, expert review, one-to-one, small group, and field test. The results of data processing on the expert validation sheet for the media are declared valid with a score of 1, at the one-to-one stage the researcher gives a questionnaire sheet to students with different abilities of high, medium, low average results obtained from 3 (three) students are 3.5 which means practical, the results of the student response questionnaire processing at the small group stage get a value of 3.16 which means practical, the results of the pretest test data processing results in an average value of 60 while the posttest is 80 then It can be seen from the learning outcomes of students at Public senior high school 1 Unggulan Indralaya Utara who obtained a value with an N-gain calculation of 0.57 which is classified as an increasing category using e-learning learning based on flipped classroom using blogs, Based on the results of the study, it can be concluded that e-learning learning based on flipped classroom using the blog that the researcher developed can be declared valid, practical, and has a potential impact on students.